Human Resource Management Strategies To Improve Company Performance In The Digital Business Era - Sulastri (International Journal of Economics, Science, and Education, 2025)
The advancement of information technology has transformed the global business landscape, compelling companies to adapt to dynamic digital business models. This shift has a direct impact on human resource management (HRM) strategies, which are a key factor in enhancing organizational performance. This study aims to analyze effective HRM strategies for addressing challenges and leveraging opportunities in the digital business era. The research method employed is a systematic literature review of 25 national and international journals published between 2018 and 2024 that discuss HRM practices in digitally based companies. The findings reveal that effective strategies include developing employees’ digital competencies through upskilling and reskilling programs, implementing data-driven HR analytics for decision-making, fostering a technology-based collaborative work culture, and adopting flexible work systems (remote and hybrid). The application of these strategies has been proven to enhance productivity, innovation, and employee satisfaction, ultimately contributing positively to organizational performance. These findings provide practical implications for managers and HR practitioners in designing HRM policies and programs that are adaptive to technological developments and market demands in the digital era.